C-Reactive Protein and Platelet-Lymphocyte Ratio as Potential Tumor Markers in Low-Alpha-Fetoprotein Hepatocellular Carcinoma - Suner, Asli; Carr, Brian I.; Akkiz, Hikmet; Karakulah, Gokhan; Uskudar, Oguz; Yalcin, Kendal; Bektas, Ahmet (Karger, 2019)
The hepatocellular carcinoma (HCC) tumor marker alpha-fetoprotein (AFP) is only elevated in about half of the HCC patients, limiting its usefulness in following the effects of therapy or screening. New markers are needed. It has been previously noted that the inflammation markers C-reactive protein (CRP) and platelet-lymphocyte ratio (PLR) are prognostically important and may reflect HCC aggressiveness. We therefore examined these 2 markers in a low-AFP HCC cohort and found that for HCCs > 2 cm, both markers significantly rise with an increasing maximum tumor diameter (MTD). We calculated the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and Youden index value for each marker, and their area-under-the-curve values for each MTD group. Patients were dichotomized into 2 groups based on the CRP and PLR from the receiver-operating characteristic curve analysis. In the logistic regression models of the 4 different MTD patient groups, CRP and PLR levels were statistically significant to estimate MTD in univariate logistic regression models of MTD groups > 2 cm. CRP and PLR were then combined, and the combination was statistically significant to estimate MTD groups of 3-, 4-, and 5-cm cutoffs. CRP and PLR thus have potential as tumor markers for low-AFP HCC patients, and possibly for screening. (C) 2018 S. Karger AG, Basel
Keywords: C-reactive protein; Platelet-lymphocyte ratio; Neutrophil-lymphocyte ratio; Hepatocellular carcinoma; Aggressiveness